Tinuy-an, The Hidden Treasure and other literary forms in barangay Burboanan - Almazan, Lilifreda; Mundiz, Teresa May A.; Salazar, Edwin C. (JPAIR Multidisciplinary Research, 2019)
This study examines the different literary forms present in Burboanan, Bislig City, where the indigenous tribe, Mandaya Kamayo, is still thriving and practicing their culture and more alongside the new one. It aimed to anthologize literary traditions found in their locality like the indigenous songs, myths, and rituals. Purposive sampling was used involving key informants such as the Mandaya leaders. A triangulation was done with a focused group discussion with the Ancestral Domain Council elders, and documentation of demonstrations on the indigenous ways of life for these people. The study found out that oral tradition is still a dominant practice in the literary scene in Burboanan. The tribe has myth on the origin of the name Tinuy-an; a collection of songs, or bagi; and rituals are done for their anito in order to ask for abundant harvests and heal sick relatives. With this information, a contextualized resource material has been developed for social science classes. The study concludes that nature played a big part in the lives of indigenous people of Burboanan, Bislig City as reflected in their literary tradition. The Mandaya Kamayo living in the area depended on nature for their sustenance, and that the belief of living harmoniously together with unseen beings is still evident.